Stellar populations in the nuclear regions of nearby radio galaxies - Aretxaga, I; Terlevich, E; Terlevich, R; Cotter, G; Diaz, A (2001)
We present optical spectra of the nuclei of seven luminous (P178MHz ≳ 1025 W Hz-1 Sr-1 ) nearby (z < 0.08) radio galaxies, which mostly correspond to the FR II class. In two cases, Hydra A and 3C 285, the Balmer and λ4000-Å break indices constrain the spectral types and luminosity classes of the stars involved, revealing that the blue spectra are dominated by blue supergiant and/or giant stars. The ages derived for the last burst of star formation in Hydra A are between 7 and 40Myr, and in 3C 285 about 10 Myr. The rest of the narrow-line radio galaxies (four) have a λ4000-Å break and metallic indices consistent with those of elliptical galaxies. The only broad-line radio galaxy in our sample, 3C 382, has a strong featureless blue continuum and broad emission lines that dilute the underlying blue stellar spectra. We are able to detect the Ca II triplet in absorption in the seven objects, with good quality data for only four of them. The strengths of the absorptions are similar to those found in normal elliptical galaxies, but these values are consistent both with stellar populations of roughly similar ages (as derived from the Balmer absorption and break strengths) and with mixed young+old populations.